International Law and Climate Change: Strengthening Global Governance, Equity, and Compliance for a Sustainable Future - Marah, Thomas Sheku (Eastasouth Institute, 2025)
Climate change constitutes one of humanity's most pressing global challenges, with far-reaching implications for economies, environments, and communities worldwide. Climate change will, therefore, require an efficient international legal mechanism in terms of eliciting international coordination and accountability, as a transboundary problem. This article looks at the role played by international conventions, including the Paris Agreement and the UNFCCC, in controlling climate change and success and failure, specifically in compliance and access in developing nations. In addition, barriers to effective compliance, including intervention gaps, financial restrictions, and political will specifically in important institutions and countries, are determined and examined. Comparatively, through academic studies, case studies, and international conventions, in this work, areas for improvement in international legislative frameworks, including increased funding, technological advancement, and creation of flexible legal frameworks for dealing with emerging environment-related concerns, are prioritized.